Aberrant monocyte subsets in patients with Behçet's disease - Li, Chaoran; Liu, Jinjing; Yu, Xin; Li, Lu; Wang, Zhimian; Shi, Jing; Zeng, Xiaofeng; Zhang, Fengchun; Chen, Hua; Zheng, Wenjie (Clinical immunology (Orlando, Fla.), 2021)
Monocytes are a versatile and dynamic population, but its implication in Behçet's Disease (BD) remains elusive. We investigated the proportion, phenotypical and functional alterations in classical monocytes (CM), intermediate monocytes (IM) and non-classical monocytes (NCM) subsets in BD. A higher IM and lower NCM population in BD patients were noted, closely correlated with disease activity, and rescued after treatment. CD11b and CD64 expression on CM, IM and NCM in BD were enhanced. BD CM promoted TNF-a and IL-6 production and facilitated Th1 differentiation. BD IM promoted IL-6 production. We further demonstrated a higher level of phosphorylated p65 (p-p65) in BD CM and increased p-p65 and p-p38 in BD IM. Our data highlighted the aberrant populations of IM and CM in BD, potentially implicated in BD' pathogenesis. •Intermediate monocytes are higher in the peripheral population and overproduce IL-6 in BD, correlated with disease activity.•Non-classical monocytes are lower in the peripheral population in BD, inversely correlated with disease activity.•Classical monocytes overproduce TNF-a and IL-6 and facilitate Th1 differentiation in BD.